Institutional Betrayal: A Structural Analysis of Prostitution Syndicates and the Erosion of Academic Integrity - Ahmad Faizal Azhar; Walim Walim; Abdullah Abdullah; Sukama Sukama (Sahabat Publikasi, 2026)
The infiltration of prostitution syndicates into the higher education ecosystem represents one of the most serious forms of institutional betrayal that threatens the moral and functional foundations of higher education as a civilized institution. This study analyzes in depth the operational structure of prostitution syndicates operating in and through academic institutions, the mechanisms of erosion of integrity that they cause, as well as the systemic institutional failures that allow this phenomenon to take place. Using a critical criminology approach with a mixed research method of legal document analysis, in-depth interviews with 38 key informants, and secondary data analysis of documented cases in Indonesia for the period 2019-2025, this study found that: Prostitution syndicates operating in the academic environment are not exogenous (from the outside) alone, but are often endogenous in nature, utilizing and being nurtured by the structural weaknesses of the institution itself, The erosion of academic integrity due to the infiltration of prostitution syndicates operates through four mutually reinforcing mechanisms: corruption of power relations, normalization of exploitation, obstruction of access to justice for victims, and destruction of institutional culture, The current institutional response is reactive, sporadic, and does not touch the structural root of the problem. This research offers the Adaptive Institutional Integrity Framework (KIIA) as a comprehensive preventive-transformative policy model.